Analysis of decapping scavenger cap complex using modified cap analogs reveals molecular determinants for efficient cap binding. (23rd October 2013) - Wypijewska del Nogal, Anna; Surleac, Marius D.; Kowalska, Joanna; Lukaszewicz, Maciej; Jemielity, Jacek; Bisaillon, Martin; Darzynkiewicz, Edward; Milac, Adina L.; Bojarska, Elzbieta
<x xml:space="preserve">Abstract</x> Decapping scavenger (DcpS) assists in precluding inhibition of cap‐binding proteins by hydrolyzing cap species remaining after mRNA 3′→5′ degradation. Its significance was reported in splicing, translation initiation and microRNA turnover. Here we examine the structure and binding mode of DcpS from Caenorhabditis elegans (CeDcpS) using a large collection of chemically modified methylenebis(phosphonate), imidodiphosphate and phosphorothioate cap analogs. We determine that CeDcpS is a homodimer and propose high accuracy structural models of apo‐ and m7GpppG‐bound forms. The analysis of CeDcpS regioselectivity uncovers that the only site of hydrolysis is located between the β and γ phosphates. Structure–affinity relationship studies of cap analogs for CeDcpS reveal molecular determinants for efficient cap binding: a strong dependence on the type of substituents in the phosphate chain, and reduced binding affinity for either methylated hydroxyl groups of m7Guo or an extended triphosphate chain. Docking analysis of cap analogs in the CeDcpS active site explains how both phosphate chain mobility and the orientation in the cap‐binding pocket depend on the number of phosphate groups, the substituent type and the presence of the second nucleoside. Finally, the comparison of CeDcpS with its well known human homolog provides general insights into DcpS–cap interactions.